METODE PENDIDIKAN ISLAM DALAM PERSPEKTIF TAFSIR: MENGKAJI PENDEKATAN PEDAGOGIS DALAM AL-QUR’AN - Hamida Olfah (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This article discusses the implementation of Islamic education methods based on tafsir in the context of contemporary education, focusing on the application of the values contained in the Qur'an in the educational process. Through tafsir approaches that include linguistic, historical, and contextual analysis, tafsir-based education aims to shape a generation that not only possesses a broad intellectual knowledge but also a strong character in accordance with Islamic teachings. Case studies in madrasah and pesantren show how this method is applied in formal and non-formal education, as well as the challenges faced in its implementation. This article also discusses the impact of the tafsir method on the development of students' character and intellect, along with suggestions to improve the quality of tafsir-based education in the future.